REFLEXIVITY AND CHANGE IN ADAPTIVE PHYSICAL ACTIVITY overcoming hubris. - Goodwin, Donna; Connolly, Maureen ([S.l.] : ROUTLEDGE, 2022)
This provocative and challenging book argues for the vital importance of critical self-reflexion in the field of adaptive physical activity (APA). It makes a powerful case for embracing discussions of the harm caused by ableist assumptions of the ideal body, maximizing capabilities and perfecting normativebased movement that dominate contemporary discourse in APA, and calls for more critical introspection about what APA is, how it is performed, and what might be needed to bring a collaborative relational ethic to this field. This book focuses on two key themes: Firstly, how ableism as a foundational belief system of APA is present in the undergraduate curriculum, professional preparation, professional practice, and organizational policies. Secondly, how to make the comfortable uncomfortable by openly debating the harm that results from non-reflexive (nondisabled) hubris in APA. The goal is to spark an exchange of ideas among scholars, practitioners, and organizational leaders and therefore to shift the paradigm from one of professional expertism to one that centres disability wisdom holders, bringing a fundamental change yo how we perform adaptive physical activity. This book is important, progressive reading for anybody with an interest in adaptive physical activity, adapted physical education, disability sport, inclusive education, the philosophy and ethics of disability and sport, or disability in wider society.
Keywords: Sports for people with disabilities; Exercise -- Physiological aspects; Kinesiology; Adaptability (Psychology); EDUCATION / Special Education / General